ASSESSMENT OF ALGERIAN TRADE EXCHANGES IN THE ARAB FREE TRADE AREA - Salah, Bougroura; Iman, Bouakaz (The journal of contemporary issues in business and government, 2024)
This research paper aims to analyze and evaluate Algerian trade exchanges with various geographical regions, with a focus on bilateral trade with Arab countries within the framework of the Greater Arab Free Trade Area. The study concluded several key findings, including a significant geographic concentration of Algerian foreign trade. Just as exports are directed towards a limited number of clients, imports into Algeria similarly come from a limited number of suppliers. Additionally, Algerian-Arab trade within the free trade agreement is extremely limited, with very low values that do not meet expectations